Las causas sociales y el impacto que genera la violencia y la delincuencia organizada en los adolescentes - Echeverría Gallardo, María José (2023)
The following work is entitled: "The social causes and the impact generated by violence and organized crime in adolescents", arose as a result of the desire to conduct an analysis due to the fact that the violation of adolescents' right to integral development and a life free of violence is evident from the increase in organized crime that has arisen in our country today, a social phenomenon which requires attention, especially when it affects a vulnerable group such as adolescents who are constantly at risk of being captured by criminal organizations. Throughout this study, both internal and external factors are considered that influence adolescents' participation in deviant behaviors. Meanwhile, it is also examined the consequences that adolescents face when they become involved in delinquency, since their involvement exposes them to a violent environment that threatens their development and rights. It is also important to recognize that an attempt is made to raise awareness of the situation faced by adolescents in which, although the State has an important role in addressing this social problem by providing prevention and rehabilitation programs and policies suitable for adolescents who break the law, it is also necessary to raise awareness of the responsibility of society as a whole, which implies the active participation of the family, communities and non- governmental organizations, as well as other actors who play a fundamental role in preventing and addressing delinquency among adolescents. This present work applied research materials such as digital and physical bibliographic sources. This research was conducted using the following methods: scientific, analytical, synthetic, inductive, deductive, hermeneutic, comparative, and statistical. Furthermore, news, cases, and statistical data were studied and analyzed using the documentary observation method. Likewise, interviews and surveys were conducted with professionals in the fields of Law, Social Work, Psychology and Criminology. Based on the results obtained, a legal and comparative analysis was undertaken with regard to the lack of public and criminal policies in the country that target solely the prevention and eradication of adolescent delinquency.